Utilization of Audacity Applications in Arabic Learning - Olivia Levans; Regar Alef; Musiion Eric (Yayasan Adra Karima Hubbi, 2022)
Today technology is developing rapidly. This development has spread to various aspects, one of which is the education aspect. Developments in the world of education are in line with technological developments. Especially in today's era of a pandemic where almost all activities are carried out from home. Alproblemsin the learning process. This raises problematics for students in understanding lessons conducted online or online, due to the limited support for learning media. Educators are required to be innovative and creative in conducting classroom learning by utilizing various available online facilities. One realization of the use of facilities by technological advances is the use of software as a learning medium. Therefore, the researcher observed the utilization of the audacity application as a learning medium for the seventh-grade students of MTSN 08 Tanah Datar in the Arabic language subject in the special field of istima'. Audacity is an audio editing application that can change audio by inserting various available effects into the audio so that it produces interesting audio. The purpose of this study is to describe the use of the Audacity application as a learning medium to attract students' interest in learning Arabic. The research also uses qualitative methods that are library research. With the utilization of the Audacity application, it is hoped that it can be a motivation for educators to continue to be creative through the many facilities born of technological advances, especially as learning media that will be an attraction for students.